Implementasi Hydrograph Programming Untuk Optimalisasi Sumber Energi Tenaga Microhydro Power Plant - Muliya, Amma; Febianto, Yoga (Jurnal Teknologi Informasi dan Masyarakat, 2024)
This study aims to evaluate the potential and performance of micro hydro power plants in the Ciasihan River, Bogor, with a measured water discharge of 0.95 m³/s, a net fall height (Hn) of 6.47 m and an average water velocity in the turbine of 0.76 m/s. This study involves the design of a turbine with dimensions of the outer diameter of the runner (Do) of 301 mm, a specific turbine speed (Ns) of 338 rpm, a radial rim width of 52.374 mm, and a total of 18 blades. The analysis shows that the potential for hydraulic electric power reaches 64.052 kW, providing an initial picture of the efficiency of converting water kinetic energy into electrical energy in a local context. To understand the performance of the power plant more comprehensively, a simulation was conducted using the Annual Energy Production Hydrograph Programming method. The simulation results show that this power plant can produce annual energy of 400.32 MWh. These findings indicate that the micro hydro power plant in the Ciasihan River has significant potential in meeting the electricity needs of isolated rural areas. This research makes a substantial contribution to the development of renewable energy in Indonesia, with a focus on the optimal utilization of locally available water resources and the application of micro hydro technology for energy sustainability.